Application of a clinical decision rule and laboratory assays in pediatrics: Adult heparin‐induced thrombocytopenia. Issue 11 (23rd August 2022) - Cohen, Omri; Lange, Kfir; Budnik, Ivan; Tamarin, Ilia; Brutman‐Barazani, Tami; Barg, Assaf Arie; Rosenberg, Nurit; Lubetsky, Aharon; Kenet, Gili; Levy‐Mendelovich, Sarina
Abstract: Background: Heparin‐induced thrombocytopenia (HIT) is rare among pediatric patients. The diagnosis of HIT depends upon clinical decision tools to assess its pretest probability, supported by laboratory evidence of anti‐platelet factor 4 (anti‐PF4)/heparin antibodies. Aims: To compare the use of the 4Ts score clinical decision tool, clinical characteristics, and laboratory findings between pediatric and adult patients with suspected HIT. Methods: We compiled all pediatric patients in our center for whom HIT testing was performed during the years 2015–2021. These were compared with a cohort of consecutive adult patients. Laboratory diagnosis of HIT was performed with particle gel immunoassay (PaGIA) as screening test and confirmed by an automated latex‐enhanced immunoturbidimetric assay (LIA) and/or by functional flow cytometry assay (FCA). Results: The cohort included 34 children (under 18 years) and 105 adults. Adults mostly received heparins for thromboembolism prophylaxis and treatment (72.4%, n = 76), and were more frequently treated with low‐molecular‐weight heparin (LMWH). Children were mostly exposed during cardiopulmonary bypass and extracorporeal membrane oxygenation (ECMO, 61.8%, n = 21), and were more frequently treated with unfractionated heparin (UFH). Compared with adults, children had significantly higher 4Ts scores. Nevertheless, adults had a slightly higher rate of a positive diagnosis of HIT. Six out of 16 adults with confirmed HIT presented with thrombosis (37.5%), whereas all three pediatric patients with HIT presented with thrombosis ( p = .087). Conclusions: 4Ts scores are higher in children compared with adult patients for whom laboratory tests for HIT were obtained. A potentially higher incidence of thrombosis in children with HIT may be attributable to the severity of underlying illness.